The impact of inflation on the financial sector development: Empirical evidence from Jordan - Khaled Batayneh; Wasfi A. Al Salamat; Mohammad Q. M. Momani (Cogent Economics & Finance, 2021)
In any economy, the financial sector plays a fundamentally important role in achieving economic growth and thus achieving sustainable economic development. Therefore, interest in this sector and the improvement of its performance is considered a strategic goal for any country. Accordingly, this study aims to analyze the short- and long-run impacts of inflation on the development of this sector on the Jordanian economy for the period from 1993 to 2018. To do so, the study uses an auto-regressive distributed lag bound testing approach, which is considered an advanced analytical model. Empirical findings confirmed that there is a statistically significant long- and short-run negative effect of inflation on financial sector development. On the contrary, there is a statistical significant long- and short-run positive impact of economic growth on financial sector performance. In addition, results confirmed that there is a positive support of the previous financial sector policies on financial sector performance in the current period.
Keywords: 330; ARDL Approach; Cointegration; Financial Sector Development; Inflation; Jordan